2013
DOI: 10.1590/s1678-86212013000300004
|View full text |Cite
|
Sign up to set email alerts
|

Identificação de práticas de gestão da segurança e saúde no trabalho em obras de construção civil

Abstract: O setor da construção civil apresenta índices de acidentes de trabalho mais elevados em relação à maioria dos demais setores industriais. Melhorias nas práticas atuais de gestão da segurança e saúde no trabalho (SST) podem trazer benefícios como a preservação da vida humana e o aumento da competitividade das empresas no mercado com a redução dos custos decorrentes de acidentes, multas e embargos. Este artigo apresenta um levantamento e uma avaliação do grau de implementação das práticas de gestão em SST e a id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
0
5
0
5
Order By: Relevance
“…When this entity exists, 59.0% report that it is the contractor or developer, 18.1% that it is the Ministry of Work and 8.2% that it is the Social Security Institute. Safety is a process that considers the use of all types of equipment and techniques to systematically guarantee the well-being of the workers [ 23 , 24 , 25 ]; therefore, the control of equipment and machinery by the company within the prevention management framework is important. Therefore, for companies in the Guatemalan construction sector, 18.0% reported that they do have an operation manual available for tools and equipment, 58.0% reported that they sometimes have one available for some of them, and 24.0% reported that one does not exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When this entity exists, 59.0% report that it is the contractor or developer, 18.1% that it is the Ministry of Work and 8.2% that it is the Social Security Institute. Safety is a process that considers the use of all types of equipment and techniques to systematically guarantee the well-being of the workers [ 23 , 24 , 25 ]; therefore, the control of equipment and machinery by the company within the prevention management framework is important. Therefore, for companies in the Guatemalan construction sector, 18.0% reported that they do have an operation manual available for tools and equipment, 58.0% reported that they sometimes have one available for some of them, and 24.0% reported that one does not exist.…”
Section: Discussionmentioning
confidence: 99%
“…Safety is a process that considers the use of all types of tools and techniques to systematically guarantee worker’s well-being [ 23 , 24 , 25 ]. Thus, the main factors that affect safety in construction companies are poor safety awareness by top management, poor training, poor safety awareness by safety coordinators and drafters of projects, reluctance to provide safety resources and reckless operations [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Bridi et al (2013) and Mariano (2008), the work accident rates in the civil construction sector are the highest when compared to other industrial sectors and this is due to the existing resistance in the use of safety equipment and failures in handling them. For Silva (2015) and Colombo (2009), many work accidents and risks in civil construction arise as a result of the lack of knowledge on the part of the worker, delays that end up generating a rush to deliver the work within the deadline agreed with the client, and for lack of observance / lack of proper planning and/or improvisation.…”
Section: Introductionmentioning
confidence: 99%
“…Entre as estratégias para a redução de acidentes do trabalho na construção, pode-se citar a adoção de práticas gestão de segurança e saúde do trabalho (SST). A prática de gestão de SST configura no processo gerencial, empregando uma ou mais técnicas e ferramentas, de características obrigatória pela legislação ou voluntária, cujo objetivo principal visa o controle de riscos relacionados à SST (BRIDI et al, 2013).…”
Section: Introductionunclassified